Dead man’s fingers point to new taxa: Two new genera of New Zealand soft corals (Anthozoa, Octocorallia) and a revision of Alcyonium aurantiacum Quoy & Gaimard, 1833 - Kessel, Gustav M.; Alderslade, Philip; Bilewitch, Jaret P.; Schnabel, Kareen E.; Norman, Jerry; Tekaharoa Potts, Romana; Gardner, Jonathan P.A. (European Journal of Taxonomy, 2022)
The taxonomic status of Alcyonium aurantiacum Quoy & Gaimard, 1833, an octocoral endemic to New Zealand, was reviewed through morpho-molecular data comparisons in an integrative approach. Molecular phylogenetic analyses (nuclear 28S and mitochondrial mtMutS) resolved New Zealand taxa as more closely related to other genera and nominal Alcyonium Linnaeus, 1758 from South America than to the genus’ North Atlantic type species. Due to low genetic variation, species delimitation relied predominantly on identifying consistent differences in sclerite and colony morphology. The former A. aurantiacum is reassigned to Kotatea gen. nov. as K. aurantiaca gen. et comb. nov. and seven new species are described in this genus (K. amicispongia gen. et sp. nov., K. lobata gen. et sp. nov., K. kapotaiora gen. et sp. nov., K. kurakootingotingo gen. et sp. nov., K. niwa gen. et sp. nov., K. raekura gen. et sp. nov., and K. teorowai gen. et sp. nov.). Three new species in Ushanaia gen. nov. are also described (U. ferruginea gen. et sp. nov., U. fervens gen. et sp. nov. and U. solida gen. et sp. nov. ). These descriptions increase our understanding of New Zealand’s endemic octocoral diversity and contribute to ongoing systematic revisions of Alcyonium.